Angular dispersion of protons passing through thin metallic films - Archubi, Claudio Darío (2005)
The angular distributions of protons after traversing thin polycrystalline Al targets (∼15 nm) with an incident energy of 10 keV have been measured and an analysis of the targets by means of transmission electron microscopy (TEM) techniques has been made. The separate influence of the different crystal characteristics and defects has been evaluated by numerical simulation considering the interaction of the ion with all the nearest neighboring atoms simultaneously. In the analysis we included the evaluation of the effects of lattice vibrations, oxide layers and foil roughness on the angular distributions. Previous experimental data in monocrystalline and polycrystalline Au targets has also been analyzed. For a consistency check a comparison with the results of the MARLOWE code for the simpler case of proton channeling in 〈1 0 0〉 Al has been performed. As in the case of Au, the present results indicate that the experiments can be explained in terms of a modified Moliere potential, and confirm the critical influence of crystal characteristics, in this case the amorphous oxide layer on the surface and the thermal vibration of the lattice atoms.